2015
DOI: 10.1002/lary.25747
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic hydrops in superior canal dehiscence and large vestibular aqueduct syndromes

Abstract: 4 Laryngoscope, 126:1446-1450, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
(42 reference statements)
1
34
1
3
Order By: Relevance
“…There was, however, one patient with underlying semicircular canal dehiscence having no evidence of EH. Patients with large vestibular aqueduct syndrome had no specific relationship between severity of their syndrome and that of EH, but these patients had overall more severe EH compared to those with semicircular canal dehiscence (33). Findings of this study support SEH being a result of third window syndromes in affected patients, however, the paucity of other studies on this topic certainly requires further investigation of this topic.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…There was, however, one patient with underlying semicircular canal dehiscence having no evidence of EH. Patients with large vestibular aqueduct syndrome had no specific relationship between severity of their syndrome and that of EH, but these patients had overall more severe EH compared to those with semicircular canal dehiscence (33). Findings of this study support SEH being a result of third window syndromes in affected patients, however, the paucity of other studies on this topic certainly requires further investigation of this topic.…”
Section: Resultsmentioning
confidence: 91%
“…A study by Sone et al has recently been published, revealing varying degrees of endolymphatic hydrops as a result of underlying semicircular canal dehiscence (33.) There was, however, one patient with underlying semicircular canal dehiscence having no evidence of EH.…”
Section: Resultsmentioning
confidence: 99%
“…For diagnosis, there are many available tests that appear to represent the abnormal pressure transmission associated with a third mobile window (ocular and cervical VEMPs, pure tone audiometry, and ECoG), nevertheless, improved CT imaging techniques such as cone beam or flat panel CT may improve diagnostic accuracy. A recent study observed that some patients with SCDS may also have endolymphatic hydrops as determined by MRI with intratympanic gadolinium (114). This observation needs to be confirmed in a larger, well-defined population, for if confirmed, it may have implications for etiology.…”
Section: Future Directionsmentioning
confidence: 99%
“…A study from Naganawa et al showed that EH can be visualized using 3-T MRI performed 4 hours after intravenous injection of gadolinium [38]. Recently, Sone et al investigated the presence of EH in subjects with EVA syndrome using 3T MRI and correlated imaging data concerning the degree of EH in the cochlea and the vestibule with clinical symptoms and hearing levels in 9 patients [39]. In this case, patient was studied using a 1.5T MRI that, due to its resolution, was unable to confirm EH; therefore, diagnosis was based on clinical and anamnestic data.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the larger benefits in hearing restoration following corticosteroid treatment were seen in the ear contralateral to EVA. One of the first reports regarding the effects of intratympanic treatment of steroids for EH showed an 80% improvement in vertigo [39]. Afterwards, several studies on intratympanic treatment for EH have been published [23, 25, 40] showing different results on hearing and vertigo: the choice of steroids, the variability of their concentration, and the outcome measurements could explain the variability of the published results.…”
Section: Discussionmentioning
confidence: 99%